Growth and Fixed Language Mindsets in Indonesian Migrant Workers (PMI) from West Kalimantan - Oktavianda, Melti; Lubis, Laila Nurfitrah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The hashtag "Kabur Aja Dulu" (Just Run Away First) trending in Indonesia reflects the growing interest of young people in becoming Indonesian Migrant Workers (PMI) abroad. In West Kalimantan, the Manpower Office (Disnaker), the Indonesian Migrant Workers Association (BP2MI), and the Job Training Institute (LPK) have provided training programs, including intensive language courses lasting at least six months as a prerequisite for employment. However, initial interviews revealed that many prospective workers withdrew due to difficulties in learning the language, which is closely related to their mindsets regarding language skills (language mindsets). This study aims to explore the fixed and growth language mindsets of PMI from West Kalimantan who have successfully completed training, passed language tests, and are now working abroad. The method used was a qualitative case study using semi-structured interviews with three PMI, supplemented by preliminary interviews with the Manpower Office and the LPK. Thematic analysis was conducted to identify patterns of beliefs and learning strategies. The results indicate that successful PMI tend to have a growth mindset, reflected in the belief that language difficulties can be overcome with practice, self-learning strategies, and social support. A fixed mindset still appears in the initial stages, but shifts toward a growth mindset through learning experiences and small successes. This finding underscores the importance of developing a growth language mindset in supporting successful language training and the adaptation of Indonesian migrant workers to international work environments.